Strengthening the capacity of millennial generation of Merapi slopes to disasters through the application of smart schools in the Logede region - Istanto Istanto; Tika Retnowati; Moordiningsih Moordiningsih; Mohamad Ali (ATTARBIYAH: Journal of Islamic Culture and Education, 2019)
Millennial generation of Merapi Slopes view that the eruption of Mount Merapi is a natural cycle, so they are required to be able to adapt to the natural environment. It is a necessity to increase the capacity of millennial generation in the context of disaster management. SMPN 2 Karangnongko applies the Smart School extracurricular in order to disseminate the values of peace and disaster management. The purpose of this study is to describe the perception of millennial generation towards disaster and the effect of the application of Smart Schools on capacity building. The study uses qualitative methods with data collection methods of observation, interviews and documentation. The results showed that the perception of millennial generation in Logede region towards disasters as tragedies, ordeal, tests, and unpleasant events that brought misery. This view is influenced by religious values and local wisdom that develops in the community.